Roles of the phagocytosis checkpoint in radiotherapy - Yulan Kui; Fan Tong; Ruiguang Zhang; Jian Wang; Xiaorong Dong (Cell Death and Disease)
Abstract Radiotherapy is widely used in cancer treatment in both curative and palliative care due to its good safety profile and broad clinical availability. It not only directly destroys tumor cells by damaging their DNA but also plays a critical immunomodulatory role, making it a potential combination partner for immunotherapy. Radiotherapy-induced immune effects are complex. They could enhance antitumor immunity by releasing tumor antigens but also promote tumor immune evasion by adaptively regulating immunosuppressive molecules, such as phagocytosis checkpoints. However, the effects of radiotherapy on phagocytosis checkpoints are not fully elaborated compared to T cell-associated immune checkpoints. Phagocytosis checkpoints are regulated by a series of receptor-ligand binding molecules, respectively on the tumor cells and phagocytes, which mediate pro-phagocytosis or anti-phagocytosis signals, modulate tumor antigen presentation, and further determine the infiltration of tumor-specific cytotoxic T cells in the tumor microenvironment. Radiotherapy regulates the different phagocytosis checkpoints on the tumor cells and phagocytes to modulate phagocytic clearance and reshape the irradiated tumor microenvironment. Therefore, radiotherapy in combination with phagocytosis checkpoints-associated immunotherapy can be a promising antitumor approach by considering the type, dose, and sequence of this combinatory regimen as well as the biomarkers for patient selection. This review attempts to summarize the cross-effects of radiotherapy and phagocytosis checkpoints and their combination strategies to enhance the efficiency of radiotherapy and improve the survival of cancer patients. Opportunities built on the roles of the phagocytosis checkpoint in radiotherapy are duly warranted.